2014
DOI: 10.1038/mt.2013.220
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virotherapy and Immunogenic Cancer Cell Death: Sharpening the Sword for Improved Cancer Treatment Strategies

Abstract: Oncolytic viruses are novel immunotherapeutics with increasingly promising outcomes in cancer patient clinical trials. Preclinical and clinical studies have uncovered the importance of virus-induced activation of antitumor immune responses for optimal therapeutic efficacy. Recently, several classes of chemotherapeutics have been shown to cause immunogenic cancer cell death characterized by the release of immunomodulatory molecules that activate antigen-presenting cells and thus trigger the induction of more po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
132
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 71 publications
(142 reference statements)
2
132
0
1
Order By: Relevance
“…6 Although not completely expected, our observations are in agreement with previous reports demonstrating that expression of DAMPs by cancer cells is observed in the course of infection by different types of viruses, including measles and Coxsackie B viruses. 1 We and others have also reported that adenoviruses induce potent autophagy in host cells. 4,7 Although the roles of autophagy during adenoviral infection have yet to be completely defined, it is clear that the autophagic process is one of the main pathways by which viral antigens are processed.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…6 Although not completely expected, our observations are in agreement with previous reports demonstrating that expression of DAMPs by cancer cells is observed in the course of infection by different types of viruses, including measles and Coxsackie B viruses. 1 We and others have also reported that adenoviruses induce potent autophagy in host cells. 4,7 Although the roles of autophagy during adenoviral infection have yet to be completely defined, it is clear that the autophagic process is one of the main pathways by which viral antigens are processed.…”
mentioning
confidence: 89%
“…1 In the current paradigm of oncolytic virotherapy, the development of an antitumor immune response is responsible for clinical success. In this model, the virus overcomes or reverses the characteristic immune evasion of solid tumors 2 and facilitates specific recognition of tumorassociated antigens (TAAs) by the host immune system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, oncolysis represents a form of immunogenic cell death, resulting in the release of potent immune-stimulatory molecules, including cytokines, pathogen-associated and damage-associated molecular patterns (PAMPs and DAMPs, respectively) and tumor-associated antigens (reviewed in [84]). This can induce recruitment of cells of both the innate and the adaptive immune system, potentially leading to systemic anti-tumor immunity.…”
Section: Modes Of Action In Oncolytic Virotherapymentioning
confidence: 99%